Self-Compassion as a Mediator Between Trauma Exposure and Suicidal Ideation - Kraus, Sabine; Torres, Jennifer (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to examine the mediating role of self-compassion in the relationship between trauma exposure and suicidal ideation among adults in the United States. Methods and Materials: A descriptive correlational design was used with a sample of 379 adult participants from the United States, selected based on the Krejcie and Morgan sampling table. Data were collected using standardized instruments: the Beck Scale for Suicide Ideation, the Life Events Checklist for DSM-5, and the Self-Compassion Scale. Descriptive statistics, Pearson correlation analysis using SPSS-27, and structural equation modeling (SEM) using AMOS-21 were employed to analyze the data and evaluate the proposed mediation model. Findings: Descriptive results indicated moderate levels of trauma exposure (M = 12.47, SD = 4.63), moderately high self-compassion (M = 81.35, SD = 13.92), and low to moderate suicidal ideation (M = 8.23, SD = 5.41). Trauma exposure was positively correlated with suicidal ideation (r = .48, p < .001) and negatively correlated with self-compassion (r = −.41, p < .001). Self-compassion was negatively correlated with suicidal ideation (r = −.52, p < .001). SEM results confirmed that self-compassion significantly mediated the relationship between trauma exposure and suicidal ideation (indirect effect: β = −0.16, p < .01), with model fit indices indicating a good overall fit (χ²/df = 2.35, CFI = 0.96, RMSEA = 0.059). Conclusion: The findings suggest that self-compassion plays a significant protective role in reducing suicidal ideation among individuals exposed to trauma. Interventions aimed at enhancing self-compassion may serve as effective strategies to mitigate the psychological effects of trauma and reduce suicide risk in diverse adult populations.